Noise Exposure and Job Stress – a Structural Equation Model in Textile Industries - Milad ABBASI; Saeid YAZDANIRAD; Ahmad MEHRI; Rohollah FALLAH MADVARI; Ahad ALIZADEH; Maryam GHALJAHI; Mohsen FALAHATI (Archives of Acoustics)
Noise exposure is one of the most important physical agents in the workplace which can induce job stress in several ways. The aim of this study was to model the interactions between independent and mediating variables and job stress using structural equation modeling. In this study, Weinstein’s noise sensitivity scale, noise annoyance questionnaire, Health and Safety Executive (HSE) job stress questionnaire and job satisfaction scale were used. To assess worker’s noise exposure, the 8-hours equivalent continuous A-weighted sound pressure level (LAeq;8 h), was measured based on ISO 9612 (2009). To achieve the aims of study, the structural equation model was run using R software 3.4.1 and Cytoscape software 3.6.0. Based on the results, while there was a direct positive correlation of noise exposure on total job stress, there were also indirect positive effects through job satisfaction and noise sensitivity as mediator variables. Using hearing protective devices negatively affected total job stress through a direct pathway and an indirect pathway when job satisfaction was a mediator variable. Regarding the total effect of noise exposure and using hearing protection devices on job stress subscales, it can be concluded that noise exposure and using hearing protection devices had greatest effect on colleagues support and demand, respectively. It can be concluded that noise exposure and lack of hearing protective devices have a significant positive effect on job stress among workers of a textile industry. In addition to the direct effect, this factor can induce job stress through noise sensitivity, job satisfaction and noise annoyance. Therefore, measures which can decrease any of the mentioned factors, also can alleviate job stress.